Combined metabolic analyses for the biosynthesis pathway of l-threonine in Escherichia coli - Yang, Qiang; Cai, Dongbo; Chen, Wenshou; Chen, Huiying; Luo, Wei (Frontiers in Bioengineering and Biotechnology, 2022)
Currently, industrial production of L-threonine (Thr) is based on direct fermentation with microorganisms such as Escherichia coli, which has the characteristics of low cost and high productivity. In order to elucidate the key metabolic features of the synthesis pathway of Thr in E. coli to provide clues for metabolic regulation or engineering of the strain, this study was carried out on an Thr over-producing strain, in terms of analyses of metabolic flux, enzyme control and metabonomics. Since environmental disturbance and genetic modification are considered to be two important methods of metabolic analysis, addition of phosphate in the media and comparison of strains with different genotypes were selected as the two candidates due to their significant influence in the biosynthesis of Thr. Some important targets including key nodes, enzymes and biomarkers were identified, which may provide target sites for rational design through engineering the Thr-producing strain. Finally, metabolic regulation aimed at one biomarker identified in this study was set as an example, which confirms that combined metabolic analyses may guide to improve the production of Thr in E. coli.